ANALYSIS OF CAPITALISM IN THE NOVEL â€œTHE GREAT GATSBYâ€ BY F SCOTT FITZGERALD (Sociology of Literature Approach) - Leiwakabessy, Avi Catherine; Ermansyah, Ermansyah (JOURNAL OF ADVANCED ENGLISH STUDIES, 2020)
This thesis is a research about analysis of capitalism in The Great Gatsby by F. Scott Fitzgerald by using sociology of literature approach. The purposes of this research were describing affect the capitalism of the novel and described Social Class to each character in the novel The Great Gatsby. This research focuses to the capitalism effects of the novel and the each character interact in different social class. The method of this research was descriptive qualitative method. The source of the data of this research was the novel The Great Gatsby by Fitzgerald which published in 1925 and consists of 9 chapter and 145 pages. While, the instrument of this research was note taking. The technique of data analysis of this research was linked to the story, concept, and method. It found two types of Capitalism in The Great Gatsby. They were effect of capitalism of the novel and social class between individual, and groups. Meanwhile social life of Gatsby, it found how Gatsby live in loneliness and still love Daisy.